Analysis of Mathematical Communication Ability on Problem-Solving Pythagoras Theorem Viewed From Students' Cognitive Style - Maslakha Diniya, Qori'; Cholily, Yus Mochamad; Zukhrufurrohmah (Journal of Teaching and Learning Mathematics, 2023)
This research is motivated by the fact that students' mathematical communication skills still need to be improved. This study aims to describe students' written and oral mathematical communication abilities toward solving the Pythagorean theorem problem in terms of field-dependent and field-independent cognitive styles in class VIII-B at SMP Al-Islam Krian. This type of research is qualitative research with a descriptive method. Subjects in this study were taken using a purposive sampling technique after carrying out the GEFT test in class VIII-B of 2 students, each based on field-independent and field-dependent cognitive styles. The instruments prepared in this study were the GEFT test, a mathematical communication skills test, and an oral examination. Based on the analysis of the answer sheets for the mathematical communication ability test and the oral test, it was concluded that students with field-independent cognitive styles have good written or oral mathematical communication skills. This can be seen from students' ability to write down and convey information, solve problems coherently, systematically, and transparently, and draw conclusions correctly. Students with field-dependent cognitive styles need better mathematical communication skills. This can be seen from the ability of students who need help to correctly write down and convey information, problem-solving ideas coherently, systematically, and clearly, as well as conclusions